Utilization of Sago Waste as an Adsorbent for the Removal of Cu(II) Ion from Aqueous Solution - P. Maheswari; N. Venilamani; S. Madhavakrishnan; P. S. Syed Shabudeen; R. Venckatesh; S. Pattabhi (E-Journal of Chemistry)
The preparation of activated carbon (AC) from sago industry waste is a promising way to produce a useful adsorbent for Cu(II) removal, as well as dispose of sago industry waste. The AC was prepared using sago industry waste with H2SO4 and (NH4)2S2O8 and physico-chemical properties of AC were investigated. The specific surface area of the activated carbon was determined and its properties studied by scanning electron microscopy (SEM). Adsorptive removal of Cu(II) from aqueous solution onto AC prepared from sago industry waste has been studied under varying conditions of agitation time, metal ion concentration, adsorbent dose and pH to assess the kinetic and equilibrium parameters. Adsorption equilibrium was obtained in 60min for 20 to 50mg/L of Cu(II) concentrations. The Langmuir and Freundlich equilibrium isotherm models were found to provide an excellent fitting of the adsorption data. In Freundlich equilibrium isotherm, the RL values obtained were in the range of 0 to 1 (0.043 to 0.31) for Cu(II) concentration of 10 to 100mg/L, which indicates favorable adsorption of Cu(II) onto Sago waste carbon. The adsorption capacity of Cu(II) (Qo) obtained from the Langmuir equilibrium isotherm model was found to be 32.467 mg/g at pH 4 ± 0.2 for the particle size range of 125–250u. The percent removal increased with an increase in pH from 2 to 4. This adsorbent was found to be effective and economically attractive.